Forensic examination of original and counterfeit medications using FTIR analysis - Hawas, Haider Radhi (2023)
The word "counterfeit" describes anything that is not genuine but is presented as or looks to be genuine in order to make or manufacture something and claim it is genuine when it is not. Commercial counterfeiting is an age-old practise that thrives in many countries and is primarily motivated by the enormous profits to be made. In regions of Africa, Asia, and the Middle East, they account for 10%-50% of all pharmaceuticals. In forensic science, a criminal could utilise these forged compounds to risk the victim's life. Because the packaging and visual appearance of the counterfeit drug are similar to those of the actual drugs, the investigator has difficulties identifying it. Little thought is given to the possibility of using counterfeit pharmaceuticals as evidence to establish a link between victim, suspect, and crime site by tracing the manufacturer information of the medications. Given the range of analytical tools available, such as chromatography and spectroscopy, differentiating counterfeit from genuine products is becoming increasingly difficult, since they provide limited information about the drug’s identity. Chemical assessment of pharmaceutical packaging and content is facilitated by further screening with FTIR spectroscopy. The aim of this study was to physically investigate and utilise attenuated total reflection Fourier transform Infrared (FTIR) spectroscopy to examine various original and counterfeit medications, including Amaryl, Aircomb, and Diamicron MR. Three counterfeit and three authentic samples of three different drugs (two anti-diabetic and one non-inflammatory) were collected from six separate manufacturers. Visual inspection was used to conduct the initial physical examination of the medication samples. The samples were then prepared for FTIR spectroscopy with potassium bromide (KBr) particle using a Spectrum 100 FT-IR (Perkin-elmer, Waltham, MA, USA) spectrometer. Physical examination of the medications revealed a plain and straightforward distinction between counterfeit and authentic medications. For various medications, the FTIR spectra revealed distinct peaks in the n fingerprint region and functional group regions, containing bonds such as O-H groups, C=O, C=C, and C-H at various wavelengths. As anticipated, the averaged spectral profiles of all studied tablet types exhibited a high degree of similarity due to their similar chemical composition. Nonetheless, there were still a few minor distinctions between the functional group arrangements. In conclusion, visual evaluation combined with FTIR spectroscopy is a highly effective method for distinguishing between distinct medication brands. The application of the technique revealed methods of forensic investigation that are rapid, robust, efficient, nondestructive, and cost-effective. Future studies with larger sample sizes may investigate the value of medication samples collected using other FTIR sampling instruments.